2022
DOI: 10.1017/s1431927621012332
|View full text |Cite
|
Sign up to set email alerts
|

Extending Estimating Hydrogen Content in Atom Probe Tomography Experiments Where H2 Molecule Formation Occurs

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Charging deuterium into APT specimens allows the distinction of experimentally introduced signals from the hydrogen background noise arising from the residual gas in the APT chamber [15] . While some studies have shown that using hydrogen charging can also provide qualitative measurements of hydrogen trapping [74] , deuterium charging has been demonstrated to reduce ambiguity in observations [15] . Furthermore, deuterium charging must be combined with voltage-pulsed APT, as laser-pulsed APT can produce a significant amount of 1 H 2 + peak at 2 m/z, leading to confusion when assigning 2 m/z to deuterium ( 2 H + ) [75] .…”
Section: Hydrogen In Metals and Alloysmentioning
confidence: 99%
“…Charging deuterium into APT specimens allows the distinction of experimentally introduced signals from the hydrogen background noise arising from the residual gas in the APT chamber [15] . While some studies have shown that using hydrogen charging can also provide qualitative measurements of hydrogen trapping [74] , deuterium charging has been demonstrated to reduce ambiguity in observations [15] . Furthermore, deuterium charging must be combined with voltage-pulsed APT, as laser-pulsed APT can produce a significant amount of 1 H 2 + peak at 2 m/z, leading to confusion when assigning 2 m/z to deuterium ( 2 H + ) [75] .…”
Section: Hydrogen In Metals and Alloysmentioning
confidence: 99%
“…The deuterium, providing a peak in the mass spectrum at 2 Da, can therefore be clearly distinguished from hydrogen in the chamber, which has a peak at 1 Da, in voltage measurements. Charging can be done by means of electrolytic charging (Barton et al, 2024;Chen et al, 2017;Haley et al, 2014) or gas phase charging (Chen et al, 2017(Chen et al, , 2019(Chen et al, , 2020Haley et al, 2017Haley et al, , 2019Ishikawa & Yoshimura, 1998;Kesten et al, 2002;Khanchandani et al, 2021Khanchandani et al, , 2022Meier et al, 2022;Takahashi et al, 2010Takahashi et al, , 2012Takahashi et al, , 2018Takahashi et al, , 2021, whereby the latter generates less contamination and is therefore preferred (Khanchandani et al, 2021). This has often been the main solution in the past.…”
Section: Introductionmentioning
confidence: 99%
“…The beauty of APT lies in the ability of detecting all elements with equal sensitivity at once, as it is based on the time-of-flight principle. Fine-scale 3D mapping of hydrogen in real space [9,10] is highly motivated by, e.g., studies of hydrogen embrittlement in metallic materials [11][12][13] and the impact of hydrogen in semiconductors [14][15][16]. APT is also used for developing hydrogen storage materials and their potential applications in catalytic reactions such as CO 2 methanation [17].…”
Section: Introductionmentioning
confidence: 99%